Enhanced surface area and thermal stability of mesoporous zirconia fibers modified by various oxides and the reinforcement mechanism. Issue 23 (1st December 2021) - Jin, Xiaotong; Yuan, Kangkang; Han, Wenjia; Wang, Xinqiang; Li, Chengshun
Abstract: In the present work, four oxides (SiO2, TiO2, LaO1.5, or CeO2 ) were selected as additives to increase the surface areas and the pore wall stability of mesoporous zirconia (ZrO2 ) fibers in virtue of enhancing the skeleton stability and hindering the grain growth. The preparation, characterization, and thermal evolution of mesoporous ZrO2 fibers incorporated with different amounts of oxide additive and simultaneously combined with heat treatment via water vapour are presented. The effects of different oxide additives on the crystallization and phase transformation of mesoporous ZrO2 fibers were investigated by X-ray diffraction. N2 adsorption-desorption studies were conducted to investigate the changes in the porous structure of the ZrO2 fibers heat-treated at different temperatures. Scanning electron microscopy confirmed the mesoporous structure of the ZrO2 fibers. The oxide-added ZrO2 fibers heat-treated in the presence of water vapour exhibited a mesoporous structure with increased surface areas and thermal stability. The related reinforcing mechanisms were proposed. It was deduced that water vapour promoted the removal of the soft template, leading to the formation of a mesoporous structure with a high surface area. Meanwhile, the increase in the surface areas of mesoporous ZrO2 fibers with the incorporation of the oxide additive was mainly due to the enhanced thermal stability of the porous walls. The relationship between the mesoporous structure stability and the zirconia phase stability was fully discussed. This work provides a new route for enhancing the surface areas and structure thermal stability of mesoporous ZrO2 fibers.